Notes on Lev Vygotsky’s “The Psychology of Art”: The Metamorphoses of Its Evaluation by Russian Psychologists - Vladimir S. Sobkin (Вестник Московского университета. Серия 14: Психология)
Background. The relevance of the work is connected with the significance of L.S. Vygotsky's early studies both for the formation of the foundations of the cultural-historical approach in psychology and theoretical and methodological principles of modern research on the psychology of art. Objectives. The aim is to determine the peculiarities of the approach to the study of aesthetic response in Vygotsky's work "The Psychology of Art". Identification of substantive aspects concerning Vygotsky's research "method" is important for studying the psychological uniqueness of artistic experience. The theoretical and ideological contexts that determine the ambiguity of assessments of "The Psychology of Art" by Russian psychologists are established. Study Participants. The original text of Vygotsky's dissertation "The Psychology of Art. Analysis of Aesthetic Reaction" (archive of the Vygodsky family), subsequent editions of "The Psychology of Art", critical articles by leading Russian psychologists on the "The Psychology of Art". Methods. Critical historical theoretical analysis, comparative textual analysis of the original text of Vygotsky's dissertation "The Psychology of Art. Analysis of Aesthetic Response" (archive of the Vygotsky family), subsequent editions of "The Psychology of Art", critical articles by leading Russian psychologists regarding "The Psychology of Art". Results. It is shown that in "The Psychology of Art" when studying the peculiarities of aesthetic reaction and cathartic experience Vygotsky uses not only the principles of structural, functional and genetic analysis of the artwork, but also a wide range of psychotechnical techniques aimed at interpreting the meaning of the artwork. At the same time, the peculiarity of his use of methodological principles of reactological and psychoanalytical approaches, models of mental experiment in analyzing psychological features of the artwork impact are revealed. It is revealed that the subsequent critical evaluations of "The Psychology of Art" were clearly influenced not only by the theoretical attitudes of various authors, but also by ideological connotations ("ideological filters", "mechanisms of social protection of the text", etc.). A shift in the substantive critical assessments of the work was recorded: from the dynamic analysis of artistic experience ("waste of energy", "explosive reaction") to the tasks of personal meaning to resolve affective contradictions arising in the perception of different levels of the organization of the artwork. It is shown that it is the attitude to the socio-biological type of human development that determines the pathos of the study of "The Psychology of Art" as a "social technique of feelings". Conclusions. In "The Psychology of Art" the main range of questions about the mechanisms of sign mediation of emotional mental processes and meaning-making is fundamentally worked out.